The Role of Alipay Platform in China's Soft Diplomacy: A Study of Chengdu Culinary Cultural Representations by Foreign Tourists - Annisa Ramadhani; Yang Nadia Miranti (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
This article analyzes the strategic role of the Alipay platform in supporting China's soft diplomacy through a case study of how foreign tourists represent Chengdu's culinary culture. The formulation of the problem in these studies on the representation of culinary culture has been widely conducted in various media, but few have highlighted the role of foreign tourists as carriers of local cultural meaning, particularly on the Alipay platform. This study examines in depth how video content uploaded by foreign tourists on the Alipay platform serves as a representational space for Chengdu's culinary identity while simultaneously positioning these tourists as cultural intermediaries in cyberspace. This study uses a qualitative, descriptive-interpretive approach. This type of research is qualitative content analysis. Data from this study includes videos, captions, and comment interactions taken directly from the accounts of three creators on the Alipay platform. The study's findings demonstrate that foreign tourists' use of the Alipay platform goes beyond facilitating transactions and has transformed into a significant tool for grassroots diplomacy. This study finds that the Alipay platform functions as a strategic medium in China's soft diplomacy by mediating the representation of Chengdu's culinary culture through video content from foreign tourists